2022
DOI: 10.1007/s10870-022-00935-3
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Approach on Experimental, Theoretical Insight of Structural Elucidation, Hirshfeld Surface Analysis, Optical and Electrochemical Properties of Acyl Thiourea-Ethynyl Hybrid Derivatives

Abstract: Hybrid moieties of ethynylated-thiourea, Th1 and Th2 have been synthesised via the addition reaction between ethynyl derivatives and 4-tert-butylbenzoyl isothiocyanate in acetone, and were characterised by selected spectroscopic methods (i.e., 1 H and 13 C NMR, UV-visible, FT-IR) and elemental analysis. Thermogravimetric analysis indicated that Th1 and Th2 were relatively stable up to ca. 210 °C. Single-crystal X-ray diffraction was used to identify the crystal structure of Th2 in which the centre of 1-acyl th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…9). 72 The preparation of solid-state Pb2+-ion selective electrodes based on PVC and liquid membranes using three 1-aroyl-3,3disubstituted thioureas as ionophores was reported by Lazo-Fraga and coworkers. 151 The electrodes showed Nernstian behavior with good sensitivities toward Pb(II) ions detection.…”
Section: Acid Dissociation Constant (Pk a )mentioning
confidence: 99%
See 1 more Smart Citation
“…9). 72 The preparation of solid-state Pb2+-ion selective electrodes based on PVC and liquid membranes using three 1-aroyl-3,3disubstituted thioureas as ionophores was reported by Lazo-Fraga and coworkers. 151 The electrodes showed Nernstian behavior with good sensitivities toward Pb(II) ions detection.…”
Section: Acid Dissociation Constant (Pk a )mentioning
confidence: 99%
“…9). 72 Single crystal XRD analysis of the 2H-1,3,5-oxadiazine-2,4(3H)-diimine derivative (30d) showed that the compound crystallized in a monoclinic crystal system and adopted the P2 1 / c space group. It was found that the oxadiazine ring in the molecule was at with an accuracy of 0.03 Å (Scheme 8).…”
Section: Molecular and Crystal Structurementioning
confidence: 99%
“…These absorptions correspond to intra ligand charge transfer associated with π!π* transitions, in perfect agreement with reported electronic spectra for 1-acyl-3-monosubstituted thiourea species. [39,40] The steady-state fluorescence emission spectrum of the complex dissolved in chloroform at ambient temperature and an excitation wavelength of 370 nm shows the occurrence of an emission broad band centered at 620 nm. Such a red shift of emission wavelength was already reported for related acylthiourea derivatives.…”
Section: Vibrational and Electronic Propertiesmentioning
confidence: 99%